War made easy : [videorecording (DVD)] : how presidents & pundits keep spinning us to death - Alper, Loretta; Earp, Jeremy; Penn, Sean, 1960-; Solomon, Norman, 1951- (Disinformation Co. Ltd., 2008)
"... exposes how presidential administrations of both parties have relied on a combination of deception and media complicity to sell one war after another to the American people. Narrated by actor Sean Penn, and based on the acclaimed book by Norman Solomon, the film exhumes five decades of remarkable archival footage to reveal in stunning detail how the American news media have uncritically disseminated, and glamorized, the pro-war messages of successive presidential administrations. The film gives special attention to parallels between the Vietnam War and Iraq, setting government spin and media collusion from the present alongside virtually identical patterns from the past. An invaluable introduction to war propaganda and public relations that transcends politics as it raises serious questions about the role of journalism and political communication in democratic societies."--Container.